Analisis Keamanan Sistem Informasi terhadap Kesalahan Hardware di SMK Tri Ratna - Andry, Johanes Fernandes; Comeron, Rion; Cristo, Natanael; Ramadhan, Ramadhan; Yosephine, Satya Howen (LPPM Universitas Bung Karno, 2023)
The development of technology and information is an inevitable update in entering the 4.0 era. Hardware is always needed in various technologies, whether computers or other technologies. Hardware can work according to its function if the computer has set the Instruction set including input, process, output, storage, and troubleshooting. Troubleshooting is one way to manage information security with the aim of ensuring the suitability of IT (Information Technology) practices by optimizing IT security policies and standard Operating Procedures (SOPs) in the use of hardware in the Tri Ratna Vocational lab. In order for the implementation of IT security policies and standard operating procedures (SOPs) to be optimized, interviews and analysis of any deficiencies and problems that often occur. Then the research team provides solutions or proposals to optimize the application of IT Security Policy, SOP and Daily Activity. Because with the application of IT Security Policy, SOP (Standard Operating Procedure) and daily activity that is precise, clear and firm, then every device available in the computer lab will be able to run according to its use and function optimally and the protection carried out against hardware can run optimally.